2018
DOI: 10.1177/0741932518795475
|View full text |Cite
|
Sign up to set email alerts
|

Aspirational Differences Between Students With and Without IEPs: Grades Earned Matter

Abstract: Using data from the 2015 Dane County Youth Assessment ( n = 12,886 students, 22 high schools), we identified disparities between students with Individualized Education Programs (IEP) and without IEPs across multiple post–high school aspirations. We identified significant IEP status × grades earned interactions in predicting students’ reported likelihood of pursuing post–high school placements. Higher reported average grades earned were more strongly associated with students’ greater reported likelihood of atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A recent national study of youth with disabilities in the United States found that more than 95% of youth with disabilities in high school (ages 15 and older) expect to have a paid job by age 30 (Lipscomb et al, 2017). This desire for future employment has been described in scores of studies addressing the aspirations of youth (e.g., Kortering et al, 2010; Rojewski et al, 2012; Sinclair & Poteat, 2020; Trainor et al, 2011). Yet, many youth with disabilities struggle to successfully navigate the pathway from high school into the workplace.…”
mentioning
confidence: 94%
“…A recent national study of youth with disabilities in the United States found that more than 95% of youth with disabilities in high school (ages 15 and older) expect to have a paid job by age 30 (Lipscomb et al, 2017). This desire for future employment has been described in scores of studies addressing the aspirations of youth (e.g., Kortering et al, 2010; Rojewski et al, 2012; Sinclair & Poteat, 2020; Trainor et al, 2011). Yet, many youth with disabilities struggle to successfully navigate the pathway from high school into the workplace.…”
mentioning
confidence: 94%